Volumetric FDG PET analysis of global lung inflammation: new tool for precision medicine in pulmonary sarcoidosis? - Adams, Human; Rooij, Rob van; van Moorsel, Coline H.M.; Spee-Dropkova, Marcela; Grutters1, Jan C.; Keijsers, Ruth G. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Currently FDG PET/CT is used as a tool for detection of active sites of sarcoidosis. Routine clinical practice relies on qualitative assessment with visual interpretation. When semi quantitatively expressed, e.g. for scientific purposes, this often leads to dichotomous “positive” or “negative” results. Metabolic activity in the lungs or mediastinum can also be expressed by SUVmax, but this measure is based only on the intensity of a single voxel. Likely for this reason these parameters show poor correlation with variables such as serum biomarkers and suboptimally predict clinical response to treatment. The current study focusses on new volumetric quantification methods for FDG PET/CT. Specifically the percentage of lung volume with increased metabolic activity, “%SUV-high”, and the average metabolic activity in the lung “SUVmean”, shows significantly better correlation with conventional biomarkers for disease activity than PET dichotomous and SUVmax. Our proposed quantification method needs subsequent and larger studies, however it may open new possibilities for future quantitative research in lung inflammation, and improve precision medicine in sarcoidosis.